ANALISIS IMPLEMENTASI PROGRAM PENGUNGKAPAN SUKARELA WAJIB PAJAK ORANG PRIBADI DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DI KPP MADYA DUA JAKARTA UTARA TAHUN 2022 - Zia Hamaz; Jiwa Pribadi Agustianto (Jurnal Ilmu Administrasi Publik, 2026)
The low compliance of individual taxpayers is indicated by the amount of assets they have domestically and/or abroad that have not been disclosed through the annual tax returns. The purpose of this study is to analyze the implementation of the Voluntary Disclosure Program for individual taxpayers in order to improve taxpayer compliance and to identify the obstacles that arise and the efforts made to overcome them. The research was conducted at the Second Intermediate Tax Office of North Jakarta using qualitative methods. Data were obtained through interviews with resource persons and documentation. The results of the study indicate hat the implementation of the Voluntary Disclosure Program has been running optimally in increasing individual taxpayer compliance. This can be seen from the value of information on the assets of individual taxpayers participating in the Voluntary Disclosure Program. However, there are still technical obstacles from internal and external parties in its implementation. To overcome this, prevention efforts are needed by providing information and directions to taxpayers in fulfilling the provisions given to minimize rrors in implementation. Keywords voluntary disclosure program, taxpayer compliance, implementation